The 2022 Updated European Association of Urology Guidelines on the Use of Adjuvant Immune Checkpoint Inhibitor Therapy for Renal Cell Carcinoma - Bedke, Jens; Albiges, Laurence; Capitanio, Umberto; Giles, Rachel H; Hora, Milan; Ljungberg, Börje; Marconi, Lorenzo; Klatte, Tobias; Volpe, Alessandro; Abu-Ghanem, Yasmin; Dabestani, Saeed; Fernández-Pello, Sergio; et al. (European urology, 2023)
In KEYNOTE-564, adjuvant pembrolizumab, a PD-1 antibody, significantly improved disease-free survival (DFS) in localised clear-cell renal cell carcinoma (ccRCC) with a high risk of relapse. In 2021, the European Association of Urology RCC Guidelines Panel issued a weak recommendation for adjuvant pembrolizumab for high-risk ccRCC as defined by the trial until final overall survival data and results from other trials were available. Meanwhile, the primary DFS endpoints were not met for adjuvant atezolizumab (PD-L1 inhibitor; IMmotion010), adjuvant nivolumab plus ipilimumab (CheckMate 914), or perioperative nivolumab (PROSPER). Owing to heterogeneity, a meta-analysis is not recommended. Pembrolizumab remains the only immune checkpoint inhibitor currently recommended in this setting. Overall survival data are immature and biomarkers to predict outcome are lacking. Uncertainty exists and overtreatment is occurring. Treatment decisions should be made with caution and with the involvement of each patient. PATIENT SUMMARY: New results from three trials of immunotherapy after surgery for kidney cancer to reduce the risk of recurrence showed no improvement with these treatments. These results are in contrast to an earlier study that showed that the antibody pembrolizumab did extend the time before kidney cancer recurrence, even though it is not yet clear if overall survival is longer. Thus, we cautiously recommend pembrolizumab as additional treatment in high-risk kidney cancer after surgery, but patient preference should be carefully considered and the risk of overtreatment should be discussed.
Keywords: Immune Checkpoint Inhibitors; Tyrosine kinase inhibitor; Neoplasm Recurrence, Local; High risk; lidé; Adjuvant; nivolumab; karcinom z renálních buněk; Kidney Neoplasms; Carcinoma, Renal Cell; Metastasectomy; inhibitory kontrolních bodů; Nivolumab; lokální recidiva nádoru; Renal cell carcinoma; nádory ledvin; Clear cell; Pembrolizumab; Humans